Double-Filtration Plasmapheresis and High-Dose Intravenous Immunoglobulin Therapy in a Case of Anti-M Alloimmunization - Yasuda, Shun; Ono-Okutsu, Miho; Fukuda, Toma; Kyozuka, Hyo; Fujimori, Keiya (American Journal of Perinatology Reports, 2024)
Hemolytic disease is a common cause of fetal morbidity and mortality. The anti-M blood cell alloantibodies are one of the most severe causes of fetal anemia and intrauterine death. Since no standard treatment method has been established for pregnant women, the management of this pathology is through conventional methods used for treating Rh blood-type alloimmunization. For the first time, we report a unique case wherein a pregnant woman who had intrauterine fetal death in two previous pregnancies with very low titers of anti-M antibodies had negative effects during very early pregnancy, which were successfully managed in her third pregnancy with a novel protocol. We aggressively managed the blood type (anti-M antibody) and blood platelet incompatibilities (anti-HPA-4b antibody) through combination therapy twice a week (46 cycles between 12 and 34 weeks) of double filtration plasmapheresis (DFPP) and high-dose γ-globulin (20–40 g/wk). An elective cesarean section was performed at 34 weeks, and a healthy neonate was born without detection of alloantibodies in the umbilical cord blood. Our report suggests that the combination of DFPP and intravenous immunoglobulin should be considered for the treatment of anti-M alloimmunization in pregnant women.
Keywords: alloimmunization; anti-M non-Rh antibody; anti-HPA-4b antibody; DFPP; high-dose IVIG